Impacts of acoustic and gravity waves on the ionosphere - Zawdie, Kate; Belehaki, Anna; Burleigh, Meghan; Chou, Min-Yang; Dhadly, Manbharat S.; Greer, Katelynn; Halford, Alexa J.; Hickey, Dustin; Inchin, Pavel; Kaeppler, Stephen R.; Klenzing, Jeff; Narayanan, Viswanathan Lakshmi; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The impact of regional-scale neutral atmospheric waves has been demonstrated to have profound effects on the ionosphere, but the circumstances under which they generate ionospheric disturbances and seed plasma instabilities are not well understood. Neutral atmospheric waves vary from infrasonic waves of <20 Hz to gravity waves with periods on the order of ten minutes, for simplicity, hereafter they are combined under the common term Acoustic and Gravity Waves (AGWs). There are other longer period waves like planetary waves in the lower and middle atmosphere, whose effects are not as important in the ionosphere as the AGWs. The most ubiquitous and frequently observed impact of AGWs on the ionosphere are Traveling Ionospheric Disturbances (TIDs), but AGWs also affect the global ionosphere/thermosphere circulation and can trigger ionospheric instabilities (e.g. Perkins, Equatorial Spread F). The purpose of this white paper is to outline additional studies and observations that are required in the coming decade to improve our understanding of the impact of AGWs on the ionosphere.